PENGARUH FINANCIAL KNOWLEDGE DAN FINANCIAL ATTITUDE TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA GENERASI MILENIAL (Studi pada Pengelola Cafe di Kota Malang) - Nabilah Muidatur Rahma; Moh. Amin; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the influence of financial knowledge and financial attitude on financial management behavior both simultaneously and partially. The population in this study is a café manager in Malang City. This research is classified as quantitative research and the data collection method uses a survey method, namely by distributing questionnaires to 100 respondents who are designated as samples. The sampling technique used in this study was non-probability sampling with purposive sampling technique. This study used primary data obtained from the results of questionnaires that had been distributed to respondents. The data analysis method in this study is to use multiple linear regression tests, as well as the tests used, namely descriptive statistical tests, instrument tests, normality tests, classical assumption tests and hypothesis tests. The results of this study show that simultaneously financial knowledge and financial attitude have a significant effect on financial management behavior. Partially, financial knowledge and financial attitude have a significant effect on financial management behavior.Keywords: Financial Knowledge, Financial Attitude, Financial Behavior